China and the World Trading System - Mattoo, Aaditya; Subramanian, Arvind (2012)
The World Trade Organization has been until recently an effective framework for cooperation because it has continually adapted to changing economic realities. The current Doha Agenda is an aberration because it does not reflect one of the largest shifts in the international economic and trading system: the rise of China. Although China will have a stake in maintaining trade openness, an initiative that builds on but redefines the Doha Agenda would anchor China more fully in the multilateral trading system. Such an initiative would have two pillars. The first is a new negotiating agenda that would include the major issues of interest to China and its trading partners, and thus unleash the powerful reciprocal liberalization mechanism that has driven the World Trade Organization process to previous successes. The second is new restraints on bilateralism and regionalism that would help preserve incentives for maintaining the current broadly non-discriminatory trading order.